Delving into the Fog of Ambiguity: An Analysis of the Trans-Pacific Partnership's Data Exclusivity Provisions and their Implications for Access to Medicines in New Zealand - Smith Diaz, Carlos Christopher (Victoria University of Wellington Law Review, 2017)
The Trans-Pacific Partnership (TPP) is a multilateral free-trade agreement which New Zealand became a party to in 2016. This article focuses on the inconsistencies that arise between the language of the TPP and New Zealand law, with respect to data exclusivity regimes. Compliance with the TPP seems to entail an extension to the terms of data exclusivity for both biologics and small-molecule pharmaceuticals. This may have the effect of impeding access to medicines by delaying the entry of competition into the market. In particular the underlying rationale behind the biologic data exclusivity provisions appears to be the protection of American corporate profits rather than the stimulation of innovation or the long-term improvement of access to healthcare. As a result, these provisions are not in New Zealand's interest and if implemented into law they may be economically detrimental.